Sustainable development of rural municipalities of the Wielkopolska Voivodship: An attempt at evaluation - Grażyna Krzyminiewska; Hanna Pondel (Economic and Environmental Studies (E&ES), 2016)
The article is an attempt at presenting the possibilities for applying one of the available research methods to the evaluation of sustainable development. The undertaken research seems to be particularly challenging to conduct due to methodology problems (in terms of the selection of indicators, the availability of data, and the evaluation of the results), however, it seems to be relatively significant for the research on sustainable development in a broader context. The aim of this study is to evaluate the sustainable development of rural municipalities of the Wielkopolska Voivodship (the Polish superior administrative unit). In the analysis of the subject matter of the study, the taxonomic method (the linear ordering method) was used, which allows extracting the areas which are similar in terms of the studied features, as well as dividing them into the regions of similar conditions for development. Having analyzed the reference data and the selected synthetic sustainable development indicators, it seems that it is the economic aspect which undermines the level of sustainability of Wielkopolska Voivodhip's rural municipalities.
Keywords: Q01; R58; 330; sustainable development; rural areas; rural municipalities; taxonomic methods